2021
DOI: 10.1109/access.2021.3068378
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Pre-Training of Imbalanced Data for Identification of Wafer Map Defect Patterns

Abstract: Visual defect inspection and classification are significant steps of most manufacturing processes in the semiconductor and electronics industries. Known and unknown defects on wafer maps tend to cluster, and these spatial patterns provide valuable process information for supporting manufacturing in determining the root causes of abnormal processes. In previous studies, data augmentation-based deep learning (DL) techniques were most commonly used for the identification of wafer map defect patterns (WMDP). Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 48 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Jain et al [9] suggested a data augmentation method using Generative adversarial networks to generate synthetic data then they used Convolutional Neural Network to classify surface defects in hot-rolled steel strips . Shon et al [10] proposed automatic data augmentation with : rotation, flipping, shifting, shearing range, and zooming techniques and deep learning method to identify defects of wafer. Zheng et al [11] developed a generic semi-supervised deep learning model for automated surface inspection using data augmentation.…”
Section: Defect Detection Methods With Data Augmentationmentioning
confidence: 99%
“…Jain et al [9] suggested a data augmentation method using Generative adversarial networks to generate synthetic data then they used Convolutional Neural Network to classify surface defects in hot-rolled steel strips . Shon et al [10] proposed automatic data augmentation with : rotation, flipping, shifting, shearing range, and zooming techniques and deep learning method to identify defects of wafer. Zheng et al [11] developed a generic semi-supervised deep learning model for automated surface inspection using data augmentation.…”
Section: Defect Detection Methods With Data Augmentationmentioning
confidence: 99%
“…Considering this, research has been conducted using unsupervised learning methods, which are useful for handling large amounts of unlabeled data. Shon et al presented a methodology to train a convolution-based variational autoencoder (CVAE) in an unsupervised manner [21], and Qiao Xu et al used unlabeled data to learn common defect patterns using an unsupervised method [22]. However, only a few studies have used pure unsupervised learning.…”
Section: Single-failure Pattern Classificationmentioning
confidence: 99%
“…Regarding our selected set of papers, the most frequently used and probably the most successful data mining method for defect product detection or classification is the Neural network. Most recently, for example, the article "Unsupervised Pre-Training of Imbalanced Data for Identification of Wafer Map Defect Patterns" written by Shon et al (2021), where the proposed model is based on convolution variational autoencoder (CVAE), achieved a 95.1% level of F-measure. In our analysis, we found out that more than 42% of composed primary studies implementing NN are focused on CNN, for example, Lin et al (2019), Wang et al (2018) 2020), Cerezci et al (2020) or Jiang et al (2021).…”
Section: • Neural Networkmentioning
confidence: 99%